National color and color designations in the poetry of A. Akhmatova (Eurasian Journal of Philology Science and Education, 2018)
This article deals with the theme of A.Akhmatova’s poetic creativity. The work describes in detail thewhole system of symbolic values, which are compared with the systems of other nations. The analysis ofcolor words in the national color, the key to the knowledge of the people, the poetic meaning, is a problematic of this text, and they perform a constructive role in texts, while performing the meaning-formingand style-forming functions. Along with this, a religious theme is shown, which is associated with shortsubjects and orthodox rituals, which makes Akhmatova’s work unique and symbolic.